Broad money demand and financial liberalization in Malaysia: an application of the nonlinear learning function and error-correction models - Mohamed, Azali; Matthews, Kent (Universiti Putra Malaysia Press, 2001)
This paper attempts to model the effects of financial liberalization and innovations on the demand for broad money in Malaysia. The nonlinear learning function and error-correction mechanism model were utilized. The results of encompassing tests and dynamic (ex post) simulation confirm the error-correction as the parsimonious specification. The augmented error-correction model with nonlinear interacted variables is unable to detect the effects of financial liberalization on Malaysian broad money demand.